Misdiagnosed Asthma Turned Out to Be Bronchial Fibroepithelial Polyp: Case Report and Review of Literature - Deeb Salahaldeen MD; Shatrit Hanin MD; Shawar Dana MD; Arman Dana MD; Wafi Khalil MD; Fatayer Mohammad MD; Abuasbeh Yousef MD (SAGE Publishing, 2024)
Bronchial fibroepithelial polyps are exceedingly rare with few cases have been reported. They can manifest with a wide array of symptoms; ranging from being totally asymptomatic, cough, refractory dyspnea, and hemoptysis. In our case, our patient's condition was diagnosed and was managed as asthma. It is one of the rare benign conditions to be encountered, shares similar morphology with other tumors such as angiomyofibroblastoma, aggressive angiomyxoma, and cellular angiofibroma. These lesions have a slow growth pattern which may end up with obstruction. According to the tumor size and symptoms caused by it, treatment varies from observation to complete resection. This case describes an incidental finding of fibroepithelial polyp in the main bronchus for a patient with long-term refractory cough for 5 years, was misdiagnosed to have asthma. Diagnosis typically involves imaging and bronchoscopy, followed by appropriate therapeutic measures and careful monitoring to assess the prognosis.